A reference method for measuring emissions of SVOCs in small chambers. (January 2016) - Wu, Yaoxing; Cox, Steven S.; Xu, Ying; Liang, Yirui; Won, Doyun; Liu, Xiaoyu; Clausen, Per A.; Rosell, Lars; Benning, Jennifer L.; Zhang, Yinping; Little, John C.
Abstract: Semi-volatile organic compounds (SVOCs) are indoor air pollutants that may have significant adverse effects on human health. Although emissions of volatile chemicals from building materials and consumer products are usually characterized in small chambers, few chamber studies have been conducted for SVOCs due to the challenges associated with analysis and the lack of validation procedures. There is an urgent need for a reliable and accurate chamber test method to verify these measurements. A reference method employing a specially-designed chamber has been developed and is undergoing extensive evaluation. A pilot inter-laboratory study (ILS) has been conducted with six laboratories performing chamber tests under identical conditions for di-2-ethylhexyl phthalate (DEHP). Results from this study showed inter-laboratory variations of 24% for DEHP emission rates, with closer agreement observed among intra-laboratory measurements for most of the participating laboratories. A mechanistic emission model fits well to the measured concentration profiles, demonstrating the feasibility of the proposed reference method to independently assess laboratory performance and validate SVOC emission tests. Highlights: A reference method that employs a special chamber and emission source is used to quantify SVOC emissions in small chambers. The study is the first inter-laboratory study for chamber tests involving SVOCs. A moderate level of agreement among inter-laboratory measurements is achieved.